The Simulation Modeling Technology of Warehouse Logistics Processes in Distributed Computing Environment (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2018)
The problem of analysis of functional and organizational structure of logistics warehouseis considered in this article and a new technology for performing such analysis is offered. Thetechnology is based on simulation modeling. In detail this technology includes methods and tools fordevelopment of simulation models, for creating problem-oriented services of the simulation modeling,for intelligent management of computing in a distributed environment. The aim of research is todevelop and realize high-level methods and tools of formulating and solving non-traditional (forconventionally used warehouse management systems) tasks using problem-oriented knowledge. Theexample of methods and tools realization to automate the simulation modeling of the logisticswarehouse is presented here. Experiments results for some tasks of the simulation modeling of thelogistics warehouse are discussed.
Keywords: simulation modeling; warehouse logistics; distributed computing environment; serviceoriented programming